Development of Edmodo-Based Evaluation Instruments on Motivation and Learning Outcomes of Natural Sciences (IPA) Students of Class V MI Muhammadiyah Cece - Munawwarah Salahuddin; Masnur Masnur; Aminullah Muhammadiyah Aminullah (Mahaguru: Jurnal Pendidikan Guru Sekolah Dasar, 2021)
This article discusses the development of an Edmodo-based evaluation instrument on the motivation and science learning outcomes of fifth grade students at MI Muhammadiyah Cece. The formulation of the problem in this study: (1) how is the design of developing an edmodo-based evaluation instrument on the motivation and learning outcomes of science students in class V MI Muhammadiyah Cece?; (2) how is the feasibility of developing an edmodo-based evaluation instrument on the motivation and science learning outcomes of class V MI Muhammadiyah Cece students based on the assessments of material experts, media experts, and learning practitioners (teachers); and (3) how is the response of students in developing an edmodo-based evaluation instrument on the motivation and learning outcomes of science students in class V MI Muhammadiyah Cece?. This study aims: (1) to determine the design of the development of an edmodo-based evaluation instrument on the motivation and learning outcomes of science students in class V MI Muhammadiyah Cece; (2) to determine the feasibility of developing an Edmodo-based evaluation instrument on the motivation and science learning outcomes of class V MI Muhammadiyah Cece students based on the assessments of material experts, media experts, and learning practitioners (teachers); and (3) to find out the response of students in the development of an edmodo-based evaluation instrument on the motivation and learning outcomes of science students in class V MI Muhammadiyah Cece.The subjects in this study were students of class V MI Muhammadiyah Cece with a total of 30 students. The data was obtained from a questionnaire, then the data was processed using analysis of validity and effectiveness. The results of this study indicate that: The results of this study indicate: 1) the development of an edmodo-based evaluation instrument is divided into: needs analysis, competency analysis, design, development, and implementation: 2) the material expert gets an average score of 4.18 (decent), from media experts get a mean score of 4.05 (decent), from teachers get an average score of 4 (decent); 3) student response questionnaires about the need or not the use of learning media get an average score of 3.35 (neutral).